Let's Investigate Maps and Scale Drawings - Smoothey, Marion (Marshall Cavendish Corporation, 1995)
These books provide a thorough and enjoyable introduction to math. The reader is encouraged to discover basic concepts through a combination of investigation, hands-on activity and theory. In many cases these activities are based on practical projects; in others the reader is encouraged to develop problem-solving strategies.
Keywords: Maps & Road Atlases; Travel